Species Diversity of Ectoparasites Recovered from Rodents at Selected Oil Palm Plantation and Paddy Fields in Western Sarawak - Yang, Lee (Universiti Malaysia Sarawak (UNIMAS), 2017)
Rodents are primary hosts to many ectoparasites, and plantation rodents are now considered the major commensal pests therefore they are needed to be taken seriously. Yet, there is limited study regarding ectoparasites on rodents from plantation areas conducted in Borneo. On the other hand, rodents serve as the zoonotic reservoirs of numerous pathogens that jeopardize human life. Therefore, the study aims to identify ectoparasites on plantation rodents, compare species diversity of ectoparasites from rodents at four localities consisting of one oil palm plantation at Kampung Tanjung Tuang, Kota Samarahan and three paddy plantations at Kampung Pueh, Sematan, Muara Tuang, Kota Samarahan and Kampung Stunggang, Lundu. A total of 54 rodent individuals of four species were captured. Sundamys muelleri was the most predominant ectoparasite-infested rodent host species with the 100% infestation rate (n=31). A total of 3921 individuals of ectoparasites comprising three hard ticks, three mesostigmatid mites, one chigger mite species and one lice species were recovered. Laelaps echidninus was the generalist species which was most common and abundant found in this study while Hoplopleura pacifica was host specific. Comparison of ectoparasite species diversities from both plantation types showed statistically significant difference (p<0.05). Thus, null hypothesis is rejected. Dermacentor sp., Haemaphysalis sp., Laelaps echidninus, Laelaps nuttalli, and Hoplopleura pacifica were some of the ectoparasite species recovered that are recognised to be potential health risk. The study has provided a useful database for ectoparasites from plantation rodents, as well as to estimate the disease outbreaks associated with rodent-borne diseases for future study.